Promising inhibitors targeting Mpro: an ideal strategy for anti- SARS-CoV-2 drug discovery (2020)
Recently, Dai W et al. published a study on Science,1 in which the two lead compounds 11a and 11b were designed and synthesized based on the features of a key enzyme Mpro of SARSCoV-2 (Fig. 1). In particular, compound 11a is a potential drug candidate for coronavirus disease 2019 (COVID-19) with strong anti-SARS-CoV-2 infection activity, good pharmacokinetics characteristics, and low toxicity. Since December 2019, the outbreak of COVID-19 caused by SARS-CoV-22 has caused a serious global public health emergency. So far, the global epidemic is still in the outbreak stage, and the number of new confirmed cases every day has exceeded 100,000 for several days. At present, the main drugs used clinically include interferon-alpha, lopinavir/ritonavir, ribavirin, arbidol, etc. However, these drugs are facing huge controversy due to the large side effects or the lack of clinical verifications of the therapeutic effects.3 Therefore, clarifying the origin and pathogenesis of pneumonia and decoding the key targets against SARS-CoV-2 are the cornerstone to design and discover safe and effective antivirus drugs.